Inseparable operations and the human operation of Christ - Duby, Steven J. (Scottish journal of theology, 2024)
The recent recovery of the teaching that the three divine persons share one operation in their outward works raises the question of whether or in what sense the human operation of Christ belongs to the Son alone. My thesis is that all three divine persons move and support the Son's human operation while the Son alone is the proper subject of his human operation. In order to substantiate this thesis, I will consider two main issues: (1) the relationship between divine movement and human energy and (2) the relationship between nature and person in Christ's human action.